The Effect of Paid Advertising and User Reviews in Marketplace on Consumer Purchase Intention through Price Perception - Ali, Mohammed Ameen Sallam; Dr. Osly Usman, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Abstract This study aims to analyze the effect of paid advertising and user reviews on consumer purchase intention in the marketplace through price perception. In the growing context of online shopping, paid advertising is considered an important tool to increase product visibility, while user reviews provide valuable information that can influence purchasing decisions. The methodology used is a quantitative approach by collecting data through questionnaires distributed to consumers. The results showed that both paid advertising and user reviews have a positive influence on price perception. Furthermore, price perception acts as a mediator that strengthens the relationship between these two variables and consumer purchase intention. These findings provide insights for businesses in designing more effective marketing strategies to attract consumers in the digital era.